2013
DOI: 10.1128/jvi.03178-12
|View full text |Cite
|
Sign up to set email alerts
|

Robust Immunity to an Auxotrophic Mycobacterium bovis BCG-VLP Prime-Boost HIV Vaccine Candidate in a Nonhuman Primate Model

Abstract: We previously reported that a recombinant pantothenate auxotroph of Mycobacterium bovis BCG expressing human immunodeficiency virus type 1 (HIV-1) subtype C Gag (rBCGpan-Gag) efficiently primes the mouse immune system for a boost with a recombinant modified vaccinia virus Ankara (rMVA) vaccine. In this study, we further evaluated the immunogenicity of rBCGpan-Gag in a nonhuman primate model. Two groups of chacma baboons were primed or mock primed twice with either rBCGpan-Gag or a control BCG. Both groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 83 publications
0
27
0
Order By: Relevance
“…Slow BCG replication rates within phagosomes and limited levels of antigen expression that peaks in the second weak after infection are factors that participate in this process [5], [30]. A previous study of ours showed that a rBCGpan-Gag prime and Gag VLPs boost vaccine regimen is highly immunogenic and induces a broad and polyfunctional central memory T cell response in baboons [10]. Other studies by Hanke et al .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Slow BCG replication rates within phagosomes and limited levels of antigen expression that peaks in the second weak after infection are factors that participate in this process [5], [30]. A previous study of ours showed that a rBCGpan-Gag prime and Gag VLPs boost vaccine regimen is highly immunogenic and induces a broad and polyfunctional central memory T cell response in baboons [10]. Other studies by Hanke et al .…”
Section: Discussionmentioning
confidence: 78%
“…When used in a prime-boost combination with a recombinant MVA expressing a matching Gag antigen, the rBCGΔ panCD expressing Gag (rBCGpan-Gag) primed higher Gag-specific CD8 + T cell responses than the wild type strain and protected against a surrogate vaccinia virus challenge [5]. In a further study we found that high levels of Gag-specific, polyfunctional CD8 + and CD4 + T cells and anti-Gag antibodies were induced in baboons primed with rBCGpan-Gag and boosted with Pr55 Gag virus-like particles [10].…”
Section: Introductionmentioning
confidence: 93%
“…In fact, among the new TB vaccine candidates under development, several are based on additional attenuations of M. bovis within the existing BCG vaccine or on attenuated M. tuberculosis strains similar to the auxotroph AMtb vaccines used here (17)(18)(19)(20)(21). Recombinant BCG strains expressing HIV antigens are also in development as potential HIV vaccines and have been tested in mice (22)(23)(24) and in adult (25)(26)(27)(28)(29) and neonatal (30) macaques. Considering the high risk of HIV and TB infection in infants, especially in sub-Saharan Africa, we deemed it important to understand how novel TB vaccines or combination HIV-TB vaccines might impact HIV acquisition.…”
mentioning
confidence: 99%
“…The most successful expression of full-length Pr 55 Gag precursor polyprotein to date was done with subtype B HIV-1 Gag in transplastomic tobacco, with yields of enveloped~100 nm diameter VLPs of up to 400 mg/kg biomass [117]. This was close to 10 000-fold more than a previous best by our group, with VLPs produced in transgenic tobacco [81], and represents a viable yield for a product with serious vaccine potential: recent evidence that lack of progression to AIDS is linked to strong CTL responses to Gag [118][119][120] reinforces the need for vaccines that can target such responses, and Pr 55 Gag VLPs are potent elicitors of CTL, especially when used as a protein boost to a heterologous prime in primate models [121,122]. A recent paper details how HIV-1 p24 antigen expressed transgenically in either Arabidopsis thaliana or Daucus carota showed a priming effect in mice fed whole plant material, eliciting humoral immune responses detected as serum anti-p24-specific IgG after an intramuscular purified p24 protein boost [123].…”
Section: Hiv Vaccinesmentioning
confidence: 93%